Effects on quality of crayfish (Procambarus clarkii) meat treated with different thermal processing methods - Liu Du; Xuan Liu; Chuanfeng Hu; Dongyin Liu; Yu Qiao; Wei Yu (Food Science of Animal Products)
This study employed four thermal processing methods to cook crayfish meat, including hot-water steaming (HS), hot-water boiling, cold-water steaming (CS), and cold-water boiling (CB). The results indicated that the four thermal treatments had varying effects on the nutritional composition, texture, microstructure, and color of the crayfish meat, as well as significant differences in the retention of volatile flavor compounds. Specifically, the cooking loss in the CB group (12.79%) was significantly higher than in the other three groups, but the retention of mineral elements was lower. Microstructural observations revealed that boiling caused more severe damage to the muscle fiber structure compared to steaming, while CB significantly increased the hardness and chewiness of the crayfish meat. The T22 signal intensity of the CB group was significantly lower than that of the other groups, indicating the greatest loss of immobile water in this treatment, while CS better retained moisture in the muscle fibers. Moreover, different cooking methods led to variations in the retention of volatile flavor compounds in the crayfish meat. Among the four methods, HS was most effective in retaining volatile flavor compounds. Overall, steaming treatments were more beneficial for preserving the nutritional components and maintaining better texture of the crayfish meat, while boiling treatments were more conducive to retaining the flavor compounds. Our findings provide valuable insights for selecting thermal processing methods for crayfish and offer useful information for the development of crayfish products.